Three stages of consumers’ multi-stage dichotomic switching process: pre-switch, switch, and post-switch - NYKANEN, Jussi (Institutional Knowledge at Singapore Management University, 2021)
This research examines why and how consumers switch their mobile phones. We propose a framework that is grounded on decision-making and motivational theories and draws on the findings from a multinational qualitative survey on consumers’ mobile phone switching process. We show that consumers’ pre-switching decisions are affected by push and pull factors, their mobile phone selections are based on utilitarian or hedonic values, and their justifications for switching are based on cognition or affect. Furthermore, we identify two archetypical routes (i.e., cognitive and affective routes) and three conjoint routes that explain the dichotomic switching processes in pre-switch, switch, and post-switch stages in which consumers rationalize their choices differently. Our study contributes to IS research by demonstrating how consumers’ reasons for initiating a switching process and selecting a replacement may differ based on an interplay of cognitive and affective elements within the process.